Let's solve each of these problems step by step using the Property of Negative Integer Exponents, which states that \( a^{-n} = \frac{1}{a^n} \).
-
Rewriting \( 15^{-38} \): \[ 15^{-38} = \frac{1}{15^{38}} \]
-
Rewriting \( 9^{-23} \): \[ 9^{-23} = \frac{1}{9^{23}} \]
-
Solving \( 3^{-4} \): \[ 3^{-4} = \frac{1}{3^{4}} = \frac{1}{81} \]
-
Generating an expression for \( 7^{-3} \cdot 7^{-5} \): \[ 7^{-3} \cdot 7^{-5} = 7^{-3 + (-5)} = 7^{-8} \] To convert it to positive exponent: \[ 7^{-8} = \frac{1}{7^8} \]
-
Generating an expression for \( \frac{5^{-9}}{4^{-12}} \): \[ \frac{5^{-9}}{4^{-12}} = 5^{-9} \cdot 4^{12} \] Rewriting \( 5^{-9} \): \[ = \frac{4^{12}}{5^9} \]
To summarize:
- \( 15^{-38} = \frac{1}{15^{38}} \)
- \( 9^{-23} = \frac{1}{9^{23}} \)
- \( 3^{-4} = \frac{1}{81} \)
- \( 7^{-3} \cdot 7^{-5} = \frac{1}{7^8} \)
- \( \frac{5^{-9}}{4^{-12}} = \frac{4^{12}}{5^9} \)